PENGARUH ROA DAN NPM TERHADAP NILAI PERUSAHAAN PADA PT. ANTAM, TBK - Chadjib Halik, Abdul (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This study aims to determine the effect of ROA and NPM on company value at PT. Antam. The research design is quantitative and associative causal with descriptive explanations. The analysis method used is multiple linear regression analysis with a sample of 11 company data for the period 2006-2016 and the type of data used is time series. The analysis shows, the average growth of Return on Assets (ROA) of PT. ANTAM for the period 2006-2016 was 54.79%. The average NPM growth was 107.37%. While the average growth in firm value is 0.16%. he results of the regression analysis showed that ROA had no significant effect on firm value with a regression coefficient value of 0.110. NPM has a positive and significant effect on firm value with a regression coefficient of 0.851. Simultaneously, ROA and NPM have a positive and significant effect on firm value with a coefficient of determination of 71.5%, while the remaining 28.5% is explained by other variables outside this study, for example liquidity ratios, activity ratios, leverage ratios, market ratios and others